The Demographic Evolution of Surinam 1920-1970 - Lamur, H. (Brill, 1973)
Indonesia
English
Keywords: Asian history; indonesia; Birth rate; Creole language; Ethnic group; Fertility; Hindustani language; Javanese people; Mortality rate; Population growth; Suriname